회주철 브레이크 디스크의 미세조직이 브레이크 떨림에 미치는 영향 연구 - 정민균; 이재영; 최진용; 김윤철; 김성진 (대한금속·재료학회지, 55(10), 2017)
Brake judder is a kind of low-frequency brake vibration and noise phenomenon generated during braking. Various types of judder have been reported, depending on the particular generation mechanism. However, the correlation between the microstructure of gray iron brake discs and judder has seldom been discussed in the literature. In this research, the effect of the microstructure of a gray iron brake disc on judder was investigated using a single end full dynamometer. Judder propensity was evaluated by measuring BTV (brake torque variation), and the effect of cell counts of eutectic gray iron on the friction surface of the brake disc was also measured in the circumferential direction. The eutectic cell counts were controlled by changing the machining thickness of the friction surface. Results showed that the microstructure of the gray iron disc played a crucial role in controlling brake vibration during braking. In this work, reduction in the eutectic cell counts resulted in less brake torque variation, suggesting more stable brake performance. (Received April 10, 2017; Accepted July 7, 2017)